A comparative study on photodegradation of twenty-three wood species after UV irradiation - Tomak, Eylem D.; Ermeydan, Mahmut A.; Can, Ahmet; Aydin, Mehmet A.; Can, Ahmet (Pergamon-Elsevier Science Ltd, 2024)
The study investigates the effect of UV irradiation on different native and exotic wood species which is an open subject of research. Thirteen native wood species and ten exotic wood species, totally twenty-three wood species, all important for wood industry in Turkey, were subjected to UVA-340nm irradiation with a constant irradiance of 0.89 W/m2/nm and a temperature of 60 degrees C for 2, 4, 8, 16, 24, 48, 72, 96, 120, 144, 168, 252 and 336 h to determine the critical degradation time for the wood species. A short exposure time (from 2h to 48h) was especially studied since the previous studies reported that important and rapid changes occurred within the initial exposure periods. The effect of UV irradiation on wood surfaces was investigated by color, surface roughness, and FTIR-ATR measurements. The results proved that UV radiation caused a rapid color change for extractive-rich wood species at the initial period of exposure (16h-48h) which decreases upon prolonged exposure. The overall color change and surface roughness were higher for native wood species in a long exposure period than for exotic ones. Elm, oak, plane, walnut, acacia and linden as native wood species, iroko, tiama, acajou, okoume, garapa, sapelli, dibetou and teak as exotic wood species were found to be more resistant to color changes in prolonged irradiation periods, probably due to content of their components especially extractives and lignin. Similar to greater color change found within the beginning of the irradiation period (16h-48h), the first 8h-24h seemed to cause a greater increase in roughness for exotic species and 16h-24h for native wood species probably due to the changes in surface chemistry. Acacia, elm, cherry, beech, tiama, teak and okoume had the highest RI whilst S. pine, ash, poplar, plane, sapelli, limba and iroko had the lowest RI among the wood species. FTIR-ATR analysis demonstrated that UV light ended up with photodegradation of lignin and photooxidation of hemicelluloses which leads carbonyl-containing chromophores, even after short-time exposures (8h-24h).
Keywords: Uv Irradiation; Color Change; Surface Roughness; Surface Chemistry; Exotic Wood; Native Wood